Cobalt Oxide Diffusion Kinetics in Ultra-Thin Amorphous Carbon Films - Robert J. Waltman (Tribology Online, 2019)
The diffusion of oxidized cobalt metal (CoOx) through a sputtered amorphous carbon film is investigated as a function of carbon film thickness and of temperature in dry air. A kinetic model is developed using the experimental data. The kinetic model is based on Fickian diffusion and includes modifications for carbon film porosity, tortuosity and for pore-clogging. The experimentally determined effective diffusion coefficient, Deff, increases with increasing temperature and decreasing carbon film thickness. However, the bulk diffusion coefficient D is independent of carbon film thickness whilst strongly dependent on temperature. The diffusibility Deff /D is thus a strong function of COC film thickness but is independent of temperature, indicative that the structure of the COC film is the significant determinant. An Arrhenius treatment yields an activation energy of 19 kcal/mol. The fitting parameters required to simulate the CoOx diffusion kinetics is tabulated. CoOx diffusion is modelled at 60°C as a function of carbon film thickness.